2007
DOI: 10.1103/physrevlett.98.057601
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in anS=1/2Chain Cuprate

Abstract: We report our discovery of ferroelectricity in the spiral-magnetic state in the quantum quasi-one-dimensional (1D) S=1/2 magnet of LiCu2O2. Electric polarization (P) emerges along the c direction below the spiral-magnetic order temperature, but changes from the c to a axis when magnetic fields (H) are applied along the b direction. We also found that P(c) increases with H(c), and P(a) appears with H(a). LiCu2O2 in zero field appears to be the first ferroelectric cuprate and also a prototypical example of the "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
404
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 368 publications
(442 citation statements)
references
References 30 publications
29
404
3
Order By: Relevance
“…When the system is polarized by an opposite electric field, P c is reversed as well, indicating the ferroelectric nature of spiral order phase [19]. However, the reported remarkable field effects on the electric polarization [7] have not been exhibited in our results.…”
Section: B Compare To Experimental Resultscontrasting
confidence: 54%
See 3 more Smart Citations
“…When the system is polarized by an opposite electric field, P c is reversed as well, indicating the ferroelectric nature of spiral order phase [19]. However, the reported remarkable field effects on the electric polarization [7] have not been exhibited in our results.…”
Section: B Compare To Experimental Resultscontrasting
confidence: 54%
“…However, based on this ab-spiral picture, the fact that the polarization emerges along the c axis can not be interpreted by the commonly accepted microscopic mechanisms: the inverse Dzyaloshinskii-Moriya interaction or spin-current model. Later, Park et al suggested another spin picture that the transverse spiral spin component was in the bc-plane [7], which is partially confirmed by Seki et al, but the quantitative calculation on the intensity of polarized neutron reflections shows a prominent discrepancy [19]. Recently, based on their own NMR and neutron diffraction data, Sato et al proposed a new noncollinear modulated magnetic structure.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…In these frustrated materials, the ferroelectricity is always induced by some special magnetic orders with the collapse of inversion symmetry, such as the collinear up-up-down-down magnetic order [3][4][5] and noncollinear spiral spin state. [6][7][8] It is noted that the anisotropy is an important factor to affect the magnetic structure, and thus plays a key role on the magnetism-driven ferroelectric behavior. Therefore, the investigation on the anisotropy is very helpful to understand the ME behavior of magnetic origin.…”
Section: Introductionmentioning
confidence: 99%